Synesthesia dan Pengalaman Seni Fotografi - Marsiano Rocky Latuny; Handry Rochmad Dwi Happy (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2023)
Photography is one branch of a large grouping in the arts, apart from design and painting. As a field of art, photography certainly has its own aesthetic concept, even the aesthetic concept is closely related to